How does construction of the healthcare data center affect the health of older adults?evidence from China - Yao, Yao; Xu, Pengyu (Frontiers in Medicine, 2025)
BackgroundThe construction of the National Healthcare Data Center (NHDC) has driven data aggregation and interoperability, and created the conditions necessary for older adults to improve their health through digital health management. This study aimed to evaluate the effect of healthcare data center construction on improving the health of the older adults and elaborate on the role of health management within the underlying mechanism.MethodsThe difference-in-differences (DID) model was used as an empirical strategy for causal identification. It included baseline regressions, robustness checks, heterogeneity analysis and mechanism analysis.ResultsThe NHDC construction significantly improves health of older adults, which is reflected in higher subjective health ratings, reduced prevalence of chronic diseases and multimorbidity, enhanced physical function, and improved mental health. Heterogeneity analysis indicates that the effect is more significant among rural residents, individuals under 60 years of age, and male seniors. Increased active health management efforts by the older adults, along with a higher likelihood of receiving health management services, play a significant role in the channels of effect.ConclusionThe construction of the healthcare data center characterized by driving data aggregation and interoperability improves the health of older adults by promoting their digital health management.